Avaliação da estratégia Saúde da Família pelos seus usuários em Municípios Rurais Paraibanos - Marcelino, Maria Quitéria dos Santos (2010)
The perception of the communities about their basic health care programs can be considered as representing its effectiveness and efficiency. The goal of the present study was to evaluate the state sponsored Family Health Strategy program (ESF) in thirty nine rural districts in the state of Paraiba-Brazil. Two non-probabilistic and equivalent samples were chosen from populations with less than 25,000 inhabitants dwelling in Paraiba s geographical regions of Zona da Mata, Agreste, Borborema, and Sertão. A Questionnaire of Evaluation of the ESF was answered by 2.956 men and women (roughly split into young, adults and elderly) community members from the above mentioned geographical areas. A factorial analysis of the ESF revealed two factors: Accessibility/host, about the relationship between the users and the family health program staff, and Structure of care, referring to the quality of the medical equipment provided by the strategy. Overall, the strategy was considered to have an average kind of performance in the two factors. The Accessibility/host factor, however, was evaluated more negatively, although not statistically significant, than the factor Structure of care, revealing a perception of more shortcomings regarding the quality of the equipment and structure available in the family health units. Finally, it was found support for the use of the Questionnaire of Evaluation of the Family Health Strategy (ESF) as an instrument useful for managers who wish to evaluate health assistance programs.